(untitled) (International Journal of Nursing Education, 2019)
Traffic accident becomes main problem with highest death rate in the world. Traffic accident requires quick and accurate management before having main emergency aid by medical workers. First aid becomes the most important aspect and immediate intervention to do by common people around the spot of accident. The fact, common people cannot promote first aid when the accident occurs due to lack of skill. Skill of common people can be improved through peer education and demonstration. This research has purpose to find out the differences about peer education method and demonstration toward skill of students in giving first aid of traffic accident. This research uses quasi experiment with pretest-posttest control groups. The respondents are 48 people grouped into two groups. The data is analyzed by using paired t-test and independent sample t-test. The findings show there is skill change of providing first aid of traffic accident by using peer education method or demonstration in which each of them gets p score 0.000. There is improvement of the skill seen on peer education group and demonstration with p score 0.000. Peer education and demonstration can be used to improve students’ skill related to providing first aid of traffic accident.